Method for bleaching and purifying black barite and application thereof

CN121894694BActive Publication Date: 2026-10-27QIANNAN NORMAL UNIV FOR NATTIES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511976493.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-25
Publication Date
2026-10-27
Estimated Expiration
2045-12-25

AI Technical Summary

Technical Problem

[0006]有鉴于此,为解决现有技术中存在将30%左右白度提升至90%以上极为困难的技术问题,本发明提供了一种黑色重晶石褪色提纯方法及其应用,通过破碎+高温煅烧+酸浸处理的协同增白工艺对黑色重晶石粉末进行处理,能够解决白度30%左右甚至更低的黑色重晶石的褪色问题,提高重晶石白度到90%以上

Benefits of technology

本发明针对白度≤30%的黑色重晶石,通过破碎+高温煅烧+酸浸处理的协同工艺,可将白度提升至≥97%,损耗率≤5%;该工艺解决了现有技术无法处理低白度黑色重晶石的盲区,有效脱除了目标致色杂质,显著提升了产品工业应用价值。本工艺操作简便、成本可控,为重晶石资源化利用提供了技术支撑,适合工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121894694B_ABST
    Figure CN121894694B_ABST
Patent Text Reader

Abstract

The application provides a black barite decoloring purification method and application thereof, and belongs to the technical field of mineral purification. The application comprises the following steps: crushing the black barite, screening the crushed barite through a 200-mesh sieve, and obtaining the crushed barite; calcining the crushed barite at 800-1000 DEG C for 1-2 hours to obtain calcined barite; and performing acid immersion treatment on the calcined barite; and after the acid immersion treatment, filtering, washing and drying are performed to obtain the purified black barite. The black barite powder is treated through the synergistic whitening process of crushing + high-temperature calcination + acid immersion treatment, the problem of decoloring of the black barite with a whiteness of about 30% or even lower can be solved, and the whiteness of the barite is improved to more than 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mineral purification technology, and in particular to a method for bleaching and purifying black barite and its application, especially suitable for processing black barite with a whiteness ≤30%. Background Technology

[0002] Natural barite exhibits a variety of colors due to differences in its formation. Based on color, barite can be classified into white, yellow, and blackish-gray barite. Due to the influence of the surrounding rocks of the main ore layer, barite from certain deposits appears blackish-gray; the surrounding rocks of these ores are mostly black siliceous rocks and black shale. The formation of black barite is related to its organic origin. Organic matter, anaerobic bacteria, and biological activity in the sedimentary environment affect the formation of barium sulfate, resulting in a typically low whiteness, sometimes as low as 20-30, severely hindering processing and application, and usually leading to its disposal as waste.

[0003] Barite is an important inorganic mineral and a strategic mineral. Due to its stable thermodynamic and chemical properties, insolubility in water and acids, non-magnetic nature, and ease of X-ray absorption, it plays a unique role in the petroleum, chemical, filler, and military industries. With industrial development, high-value-added barite products are continuously being developed, its application areas are constantly expanding, and its market prospects are broad.

[0004] To improve the utilization rate and added value of low-grade barite such as yellow ore, physical and chemical methods are typically used to purify and process low-grade, high-impurity, and low-whiteness barite minerals, giving them new functions and uses and enhancing their utilization value. Common physical purification and whitening methods include hand sorting, magnetic separation, gravity separation, and flotation, while chemical methods mainly include acid leaching, alkali leaching, and redox reactions. For ores with large differences in particle size distribution and simple impurity occurrence forms, physical purification is usually more effective; however, for ores with complex impurity composition and difficult separation, chemical treatment is required. For example, Li Xueqin used an acid-alkali leaching method combined with a complexing agent to remove coloring substances, increasing the whiteness from 57.8% to 84.7% and the BaSO4 content from 95.6% to 97.3%; Xiao Qin used a Na2S2O4 reduction method with EDTA complexing agent for whitening, but the whiteness only reached about 81.0%.

[0005] The above method is generally applicable to raw ore with a whiteness of about 50%, and can make the final whiteness reach about 80%, an increase of about 30%. It is mainly for low organic matter and iron-containing yellow barite, but it is not very effective for high organic matter black barite with a whiteness of less than 30%, especially it is extremely difficult to increase the whiteness from about 30% to more than 90%. Summary of the Invention

[0006] In view of this, in order to solve the technical problem that it is extremely difficult to improve the whiteness of black barite from about 30% to over 90% in the existing technology, the present invention provides a method for bleaching and purifying black barite and its application. By processing black barite powder through a synergistic whitening process of crushing + high-temperature calcination + acid leaching, the bleaching problem of black barite with a whiteness of about 30% or even lower can be solved, and the whiteness of barite can be improved to over 90%.

[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for bleaching and purifying black barite, comprising the following steps: Step (1): Crush the black barite and sieve it through a 200-mesh sieve to obtain the crushed barite; Step (2): Calcine the crushed barite at 800~1000℃ for 1~2 hours to obtain calcined barite. Step (3): Acid leaching treatment is performed on the calcined barite; Step (4): After the acid leaching treatment is completed, the sample is filtered, washed and dried to obtain the purified black barite.

[0008] Preferably, in step (2), the crushed barite is calcined at 800°C for 1 hour to obtain calcined barite.

[0009] Preferably, the acid leaching treatment uses a single acid system or a mixed acid system.

[0010] Preferably, a single acid system is used for treatment, employing either 5% hydrofluoric acid or 45% sulfuric acid.

[0011] Preferably, in step (3), the mixed acid system treatment uses a mixed solution of sulfuric acid, hydrofluoric acid and distilled water in a ratio of 2mL:1g:3mL.

[0012] Preferably, in step (3), the mixed acid system treatment uses a mixed solution of sulfuric acid, hydrofluoric acid and ammonium fluoride, with a mass ratio of 8:5:17.5.

[0013] Preferably, in step (3), the mixed acid system treatment includes a first acid leaching treatment and a second acid leaching treatment; The first acid leaching treatment uses a mixed solution of sulfuric acid, hydrofluoric acid and ethane-1-hydroxy-1,1-diphosphoric acid, with a mass ratio of 6:3:10. The second acid leaching treatment uses a mixture of sulfuric acid, hydrofluoric acid, and ethane-1-hydroxy-1,1-diphosphoric acid in a mass ratio of 5:1:15.

[0014] Preferably, the temperature of the first acid leaching treatment is 60-100℃, and the time is 60 minutes; The second acid leaching treatment is carried out at a temperature of 60-120℃ for 60 minutes.

[0015] Secondly, the present invention also provides the application of the above-mentioned black barite bleaching and purification method in the treatment of black barite with a whiteness ≤30%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention targets black barite with a whiteness ≤30%. Through a synergistic process of crushing, high-temperature calcination, and acid leaching, the whiteness can be increased to ≥97%, with a loss rate ≤5%. This process overcomes the limitations of existing technologies in handling low-whiteness black barite, effectively removing target coloring impurities and significantly enhancing the industrial application value of the product. The process is simple to operate, cost-controllable, and provides technical support for the resource utilization of barite, making it suitable for industrial production. Attached Figure Description

[0017] Figure 1 This is a graph showing the mass change of barite treated with hydrofluoric acid in Experiment 3. Figure 2 The graph shows the change in whiteness of barite treated with hydrofluoric acid in Experiment 3. Figure 3 The graph shows the change in whiteness of barite after sulfuric acid treatment; Figure 4 This is a graph showing the mass change of barite after sulfuric acid treatment. Figure 5 A graph showing the change in whiteness of barite after treatment with a mixed acid (hydrofluoric acid); Figure 6 The graph shows the mass change of barite after treatment with mixed acid (hydrofluoric acid); Figure 7 The graph shows the change in whiteness of barite after treatment with mixed acid (sulfuric acid); Figure 8 The graph shows the mass change of barite after treatment with mixed acid (sulfuric acid). Detailed Implementation

[0018] This invention provides a method for bleaching and purifying black barite, comprising the following steps: Step (1): Crush the black barite and sieve it through a 200-mesh sieve to obtain the crushed barite.

[0019] Step (2): Calcine the crushed barite at 800~1000℃ for 1~2 hours to obtain calcined barite. In this invention, it is preferable to calcine at 800℃ for 1 hour to obtain calcined barite.

[0020] Step (3): Acid leaching treatment is performed on the calcined barite. In this invention, the acid leaching treatment adopts a single acid system or a mixed acid system. For the single acid system treatment, a 5% hydrofluoric acid treatment or a 45% sulfuric acid treatment is preferred. In the mixed acid system treatment, the treatment effect is improved by adding composite additives, preferably ethane-1-hydroxy-1,1-diphosphonic acid (HEDP), ascorbic acid, oxalic acid, hydrofluoric acid, etc. In the mixed acid system treatment, a mixed solution of sulfuric acid, hydrofluoric acid and distilled water is used, with a ratio of 2mL:1g:3mL. Or, in the mixed acid system treatment, a mixed solution of sulfuric acid, hydrofluoric acid and ammonium fluoride is used, with a mass ratio of 8:5:17.5. Alternatively, the treatment may involve a mixed acid system, including a first acid leaching treatment and a second acid leaching treatment. The first acid leaching treatment uses a mixed solution of sulfuric acid, hydrofluoric acid, and ethane-1-hydroxy-1,1-diphosphoric acid in a mass ratio of 6:3:10. The second acid leaching treatment uses a mixed solution of sulfuric acid, hydrofluoric acid, and ethane-1-hydroxy-1,1-diphosphoric acid in a mass ratio of 5:1:15. Preferably, the temperature of the first acid leaching treatment is 60-100°C, and the time is 60 minutes; the temperature of the second acid leaching treatment is 60-120°C, and the time is 60 minutes.

[0021] Step (4): After acid leaching, the sample is filtered, washed, and dried (110℃, 1h) to obtain purified black barite. The above-mentioned black barite bleaching and purification method provided by the present invention is applicable to the treatment of black barite with a whiteness ≤30%.

[0022] This invention addresses the problem of low whiteness and purity in barite due to the presence of coloring impurities such as iron oxide, manganese oxide, and carbonaceous materials. This technology develops a synergistic whitening process combining acid leaching and high-temperature calcination for treating different barite powders. Acid systems such as hydrochloric acid, hydrofluoric acid, and sulfuric acid are used to react with metal oxides to generate soluble salts. These salts are then removed by filtration and water washing to remove the metal impurities. High-temperature calcination is used to volatilize the carbonaceous impurities. The effects of calcination parameters, acid leaching system, and the type and amount of additives on the whitening effect were systematically investigated. Product performance was evaluated using whiteness, blue phase value, and α-value (a red-green hue index). Results show that under optimized process conditions, the whiteness of barite can reach 90.5, and the α-value can be as low as 0.7, effectively removing the target coloring impurities and significantly improving the industrial application value of the product. This process is simple to operate and cost-effective, providing technical support for the resource utilization of barite.

[0023] To obtain suitable process parameters, the present invention conducted the following experiments on black barite with a whiteness ≤30%: Experimental reagents and instruments Reagents: Hydrofluoric acid (40%), sulfuric acid (98%), high-fluoride waste acid (mainly containing hydrofluoric acid and hydrochloric acid) Instruments: heating plate, stirrer, drying oven, LC-WSB-2 whiteness meter, WSC-2B portable precision instrument Colorimeter, muffle furnace, electronic balance, pulverizer, 200-mesh sieve, filtration device (vacuum pump, Buchner funnel, filtration flask), etc.

[0024] Experimental steps 1. Barite sample pretreatment ① Place the barite solid into the crusher and crush it (5 rotations). If the crusher temperature gets too high during the crushing process, stop operating immediately, as the crusher is prone to burnout under high temperatures. After crushing, let it stand for 20 minutes. When opening the crusher lid, open it slightly to release air before fully opening it to prevent dust explosion.

[0025] ② Sieve the obtained barite powder through a 200-mesh sieve, pack the product into a sample bag and label it (barite powder is less than 200 mesh).

[0026] 2. Whitening effect of black barite powder (1) Calcination ① Weigh the empty, covered crucible (G) 12 ); ② Take 700g (G) 13 Gray barite powder (less than 200 mesh) was added to the weighing crucible mentioned above and weighed (G). 14 It was then placed in a muffle furnace and calcined at 1000°C for one hour. ③ After the reaction is complete, weigh it (G). 15 The product is placed in a mortar and ground, and then weighed (G). 16 ), measure whiteness; (2) First acid leaching (hydrochloric acid waste acid, composed of hydrochloric acid + hydrofluoric acid + impurities) ① Take 2*G 16 Place g of waste acid into a 2000ml PTFE beaker for later use; ② Add the product obtained above into a PTFE beaker containing waste acid, place it on a heating plate and heat (temperature between 95-105℃) and stir with a stirrer for one hour; ③ After the reaction is complete, cool it to room temperature, pour the supernatant into the waste liquid bucket, and add deionized water to the PTFE beaker to dilute the waste acid and prevent the filter paper from being corroded and penetrated during filtration. ④ Before vacuum filtration, weigh the evaporating dish and two sheets of filter paper (used during vacuum filtration) (G). 17 Rinse with 21,000 ml of deionized water; ⑤ After filtration, place the filter residue and filter paper into the weighed evaporating dish, and dry it in a drying oven (75℃). Record the weight of the evaporating dish, filter paper, and filter residue after drying (G). 18 ); ⑥ Grind the filter residue in a mortar and pestle, and weigh it (G). 19 ), measure its whiteness; (3) Second acid leaching (mixed sulfuric acid) ① Prepare a mixture of hydrofluoric acid and sulfuric acid (barite powder: hydrofluoric acid: sulfuric acid: water = 2g: 1g: 2g: 7g), and put it together with the above filter residue into a PTFE beaker. Place the beaker on a heating plate and heat it (temperature between 95-105℃) and stir it with a stirrer for one hour. ② After the reaction is complete, cool it to room temperature, pour the supernatant into the waste liquid bucket, and add deionized water to the tetrafluorobenzene beaker to dilute the high-fluoride waste acid and prevent the filter paper from being corroded and penetrated during filtration. ③ Before vacuum filtration, weigh the evaporating dish and two sheets of filter paper (used during vacuum filtration) (G). 20 Wash with 21,000 ml of deionized water; ④ After filtration, place the filter residue and filter paper into the weighed evaporating dish, and dry it in a drying oven (75℃). Record the weight of the evaporating dish, filter paper, and filter residue after drying (G). 21 ); ⑤ Grind the filter residue in a mortar and pestle, and weigh it (G). 22 ), and measure its whiteness.

[0027] (4) Experimental data processing Grey barite:

[0028] That is, calcination loss rate = [sample mass before calcination - (total weight before calcination - total weight after calcination)] Sample quality 100%.

[0029]

[0030] That is, the loss rate after a single acid leaching = [sample mass before acid leaching - (total weight before acid leaching - total weight after acid leaching)] Sample quality 100%.

[0031]

[0032] That is, the loss rate after a single acid leaching = [sample mass before acid leaching - (total weight before acid leaching - total weight after acid leaching)] Sample quality 100%.

[0033]

[0034] Total loss rate = sum of the three loss rates.

[0035] Experiment 1 investigates the effect of experimental reaction conditions on the whiteness of the product, as detailed below: Composition of raw material barite

[0036] 1. Effect of calcination temperature on gray barite 50g of gray-black barite was used to treat gray barite powder following the steps of calcination and first acid leaching, but the calcination temperatures were 600℃, 800℃, and 1000℃ respectively. Whiteness was used as the evaluation index, and the results are shown in Table 1.

[0037] Table 1. Calcination effects at different temperatures

[0038] As shown in Table 1, the whiteness of black barite is highest at 800℃, therefore the calcination temperature should be 800℃.

[0039] Experiment 2: The influence of other parameters, as detailed below: 1. Medicines and instruments Chemicals: Sulfuric acid, hydrofluoric acid, hydrochloric acid, waste acid, ammonium fluoride (NH4F), sodium citrate, HEDP, etc. (industrial grade or analytical grade) Instruments: muffle furnace, heat-collecting constant-temperature stirrer, constant-temperature water bath, electronic balance (accuracy 0.01g), suction flask, crucible, evaporating dish, Hunter whiteness meter (detection accuracy ±0.01). 1.2 Experimental Procedure 1.2.1 Treatment of black barite with mixed acids (1) Configure four types of mixed acid systems: ① Sulfuric acid-hydrofluoric acid-distilled water (150mL:75g:225mL); ② Sulfuric acid-hydrofluoric acid-NH4F (200g:125g:437.5g); ③ Sulfuric acid-hydrofluoric acid-HEDP (single immersion: 120g:60g:200g, double immersion: 50g:10g:150g); ④5% hydrofluoric acid + 30% hydrochloric acid (waste acid): Weigh 10g of black barite powder into each beaker and add 50mL of the corresponding mixed acid.

[0040] (2) Place in an 80℃ water bath or electric hot plate for heating and stirring. For a single acid immersion, soak for 1 hour. For a second acid immersion, filter after the first acid immersion and then add freshly prepared second acid solution and stir for 30 minutes.

[0041] (3) After filtration, wash with distilled water until neutral, dry at 105℃ for 2 hours, grind through a 200-mesh sieve, weigh, and test the whiteness, blue phase whiteness value and a value (color difference index of color).

[0042] (4) Weigh and photograph the black barite block (26.54g / 29.91g), then place it in 5% hydrofluoric acid or a mixture of 5% hydrofluoric acid and 30% hydrochloric acid, stir in an 80°C water bath for 1 hour, wash with water until neutral, dry at 105°C for 2 hours, weigh and photograph it.

[0043] 1.2.2 Calcination-Acid Leaching Co-treatment (1) Weigh out black barite powder (10g / 150g / 250g), add 0.1g, 0.3g and 0.5g of different types of additives, mix well and put into a covered crucible.

[0044] (2) Place it in a muffle furnace and calcine at 1000℃ for 40 min, 1 h and 2 h respectively. After naturally cooling to room temperature, weigh it and calculate the loss rate (loss rate = (weight before calcination - weight after calcination) / weight before calcination × 100%).

[0045] (3) The calcined sample was placed in a composite acid leaching system consisting of sulfuric acid-hydrofluoric acid-HEDP for one and two acid leachings. The sample was stirred in a water bath at 80°C for 1 hour, filtered, washed with water until neutral, dried at 105°C, and then iron was absorbed again to detect whiteness, blue phase value and a value.

[0046] 1.2.3 Effects of Variables on Experiments (1) Additive variables: Additives such as sodium citrate were set up with dosage gradients of 0.1g, 0.3g, and 0.5g, and a blank group (no additives) was used in parallel experiments.

[0047] (2) Calcination time variable: with a fixed temperature of 1000℃, gradients of 40min, 1h and 2h were set to investigate the effect on impurity removal and whiteness.

[0048] (3) Acid leaching system variables: Compare the treatment effects of mixed acid, waste acid and composite acid systems, and record the product color and performance indicators.

[0049] 2. Experimental Results 2.1 Treatment of black barite with mixed acids Table 2. Experimental treatment of black barite with mixed acids.

[0050] 2.3 Comparison of typical sample performance (Table 3) Table 3 Comparison of typical sample performance

[0051] 3. Results Analysis In single acid treatment, hydrofluoric acid has a significantly better whitening effect than sulfuric acid: the whiteness reaches 80.12 after treatment with 5% hydrofluoric acid, while the whiteness is only 76.12 after treatment with 45% sulfuric acid. However, increasing the concentration of hydrofluoric acid will lead to a sharp increase in the loss rate (61% loss at 25% concentration), which is less economical.

[0052] The mixed acid system is more effective than the single acid system: the sulfuric acid-hydrofluoric acid-HEDP secondary acid leaching system is the best, with a whiteness of 97.42 and an a value of 0.133, and deep removal of Fe and Mn impurities; the waste acid system has a whiteness of only 65.23 due to impurities interfering with the reaction, and the product is jade yellow.

[0053] The optimal calcination time is 800℃ for 1 hour: at this time, carbonaceous impurities are fully volatilized, metal oxides are completely transformed, and whiteness reaches over 90. Calcination for 40 minutes does not completely remove impurities, and calcination for 2 hours increases the loss rate to 2.97% and does not significantly improve whiteness.

[0054] The optimal process is "calcination at 800℃ for 1 hour + first acid leaching (120g sulfuric acid + 60g hydrofluoric acid + 200g water) + second acid leaching (50g sulfuric acid + 10g HEDP + 150g water)", resulting in a product with a whiteness ≥97 and a loss rate ≤5%, meeting the requirements of high-end industrial applications.

[0055] Experiment 3: Decolorization experiments of single and mixed acids, such as... Figure 1-8 As shown 1. Experiment 1.1 Medicines and Instruments Hydrofluoric acid, sulfuric acid, hydrochloric acid Heat-collecting constant-temperature stirring device, WSC-2B portable precision colorimeter, etc.

[0056] 1.2 Experimental Procedure 1.2.1 Treatment of barite with a single acid Prepare hydrofluoric acid solutions of different mass concentrations by weighing 10g of barite powder into a PTFE beaker and adding 50mL of hydrofluoric acid solution of different mass concentrations.

[0057] Then place it in an 80℃ water bath and stir for 1 hour, filter, and wash with distilled water until neutral.

[0058] The obtained sample was dried, ground, weighed, and its whiteness was measured.

[0059] The experiment was conducted using sulfuric acid of different mass concentrations following the same procedure.

[0060] 1.2.2 Treatment of barite with mixed acids Prepare mixed acids of sulfuric acid with the same and different mass concentrations of hydrofluoric acid. Weigh 10g of barite powder into a tetrafluoroethylene beaker and add 50mL of mixed acid of different concentrations to each.

[0061] Then place it in an 80℃ water bath and stir for 1 hour, filter, and wash with distilled water until neutral.

[0062] The obtained sample was dried, ground, weighed, and its whiteness was measured.

[0063] The experiments were conducted using the same steps for a mixture of sulfuric acid of the same mass concentration and hydrofluoric acid of different mass concentrations, and a mixture of 5% hydrofluoric acid and 30% hydrochloric acid.

[0064] Prepare 5% hydrofluoric acid by weighing and photographing a barite block, placing it in a PTFE beaker, and adding 50 mL of 5% hydrofluoric acid.

[0065] Then place it in an 80℃ water bath and stir for 1 hour.

[0066] Wash the obtained stones until neutral, dry them, weigh them, and take photos.

[0067] The experiment was conducted using a mixture of 5% hydrofluoric acid and 30% hydrochloric acid (waste acid) following the same procedure.

[0068] 1.2.3 Effect of water bath temperature Prepare a 10% hydrofluoric acid solution. Take a picture of the barite block, place it in a PTFE beaker, and add 50 mL of 10% hydrofluoric acid solution.

[0069] Then heat without water bath and let stand for 1 hour.

[0070] Wash the obtained stones until neutral, dry them, and photograph them.

[0071] Next, place the stone into a PTFE beaker and add 50 mL of 10% hydrofluoric acid.

[0072] Then place it in an 80℃ water bath and stir for 1 hour.

[0073] Wash the obtained stones until neutral, dry them, and photograph them.

[0074] The same procedure was followed using 10% sulfuric acid.

[0075] 1. The results are as follows: 2.1 Treatment of barite with a single acid

[0076] 2.2 Treatment of barite with mixed acids

[0077] The test results in the table above show that: 1. For the treatment of barite with a single inorganic acid, hydrofluoric acid treatment is more effective (it has a significant effect on barite treated with 5% hydrofluoric acid and the highest whiteness is about 80.000) than sulfuric acid treatment (it has a significant effect on barite treated with 30% sulfuric acid and the highest whiteness is about 76.000). However, the loss is relatively large when treating barite with hydrofluoric acid and hydrofluoric acid is more expensive. Therefore, an experiment was conducted to investigate the treatment of barite with a mixture of hydrofluoric acid and sulfuric acid.

[0078] 2. When exploring mixed inorganic acids, when sulfuric acid and hydrofluoric acid are mixed, hydrofluoric acid plays a dominant role, while sulfuric acid can play a role, but its role is not significant.

[0079] In the investigation of mixed inorganic acids, it was found that a mixture of hydrochloric acid and hydrofluoric acid (waste acid) can replace pure hydrofluoric acid. The mixture of hydrochloric acid and hydrofluoric acid can further improve the whiteness of the treated barite, and the loss rate is also low.

[0080] 3. During the investigation of temperature, it was found that increasing the temperature deepened the reaction between inorganic acid and barite, which improved the whiteness of the treated barite.

[0081] The above description is merely a preferred embodiment of the present invention. However, the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for bleaching and purifying black barite, characterized in that, Includes the following steps: Step (1): Crush the black barite and sieve it through a 200-mesh sieve to obtain the crushed barite; Step (2): Calcine the crushed barite at 800~1000℃ for 1~2 hours to obtain calcined barite. Step (3): The calcined barite is subjected to acid leaching treatment. The acid leaching treatment adopts a mixed acid system, which includes a first acid leaching treatment and a second acid leaching treatment. The first acid leaching treatment uses a mixed solution of sulfuric acid, hydrofluoric acid and ethane-1-hydroxy-1,1-diphosphoric acid, with a mass ratio of 6:3:

10. The second acid leaching treatment uses a mixture of sulfuric acid, hydrofluoric acid and ethane-1-hydroxy-1,1-diphosphoric acid, with a mass ratio of 5:1:

15. Step (4): After the acid leaching treatment is completed, the sample is filtered, washed and dried to obtain the purified black barite.

2. The method for bleaching and purifying black barite according to claim 1, characterized in that, In step (2), the crushed barite is calcined at 800℃ for 1 hour to obtain calcined barite.

3. The method for bleaching and purifying black barite according to claim 1, characterized in that, The temperature for the first acid leaching treatment is 60-100℃, and the time is 60 minutes. The second acid leaching treatment is carried out at a temperature of 60-120℃ for 60 minutes.

4. The application of the black barite bleaching and purification method according to any one of claims 1-3 in the treatment of black barite with a whiteness ≤30%.

Citation Information

Patent Citations

  • Method for preparing ultrafine high-whiteness active barite powder

    CN102616824A

  • Purification and whitening process of fine barite powder

    CN111252794A